Assessment of the Effect of Replacing Normal Aggregate by Porcelinite on the Behaviour of Layered Steel Fibrous Self-Compacting Reinforced Concrete Slabs under Uniform Load - Ahmed S. D. AL-Ridha; Ali A. Abbood; Ali F. Atshan (Journal of Engineering)
In this research, an attempt has been made to study the effect of replacing all normal-weight aggregate “NWA” by lightweight aggregate “LWA” (having a volume equal to 60% of the volume of normal-weight aggregate) on the behaviour of layered steel fibrous self-compacting reinforced concrete slabs with various volume fractions of steel fiber under uniform area load using fine sand technique. The experimental work consists of two groups “NWA” and “LWA,” each group consists of three slab specimens (having an aspect ratio equal to the golden ratio, i.e., 1.618), the thickness of each slab is divided into two equal layers, the top layer is free from steel fibers, while the steel fibers exist only in the bottom layer with three volume fractions (0%, 0.4%, and 0.8%). Ultimate uniform load of the slabs decreases with the increase in steel fiber content, while the percentage of decrease in the bulk density remains rather constant. It was also found that the ultimate uniform load of the slabs in each group is significantly improved with increasing steel fiber content, and the percentage of this improvement is higher in lightweight concrete “LWC” than in normal-weight concrete “NWC” Finally, it was noticed that when steel fiber increased, the flexural strength of slabs increased higher than shear strength; therefore, the mode of failure has been changed from bending to shear mode for slabs of both groups “NWC” and “LWC.”